Development of Non-Contact Fatigue Crack Propagation Monitoring Method Using Air-Coupled Acoustic Emission System - MATSUO, Takuma; HATANAKA, Daisuke (Engineering Transactions, 2019)
A monitoring system for fatigue crack propagation was developed using a non-contact acoustic emission (AE) monitoring system. The AE signals generated during the plane bending fatigue test were first monitored. The AE generation rate increased after approximately 0.5 of the fatigue life ratio. The maximum amplitude of the AE signals increased with a tendency similar to that of the crack propagation. The sensor sensitivities for the flat and arced surfaces were then compared. The sensitivity improved when the specimen surface was flat. The bar specimen with plane surfaces was used for the AE monitoring of the rotary bending fatigue test. From 0.715 of the fatigue life ratio, the AE generation rate increased after crack generation. The AE signals were detected at an earlier stage of the fatigue life in the flat surface specimen compared with the arc surface specimen during the rotary bending fatigue test. The detection of fatigue cracks in the rotary component at an early stage was possible using a non-contact AE monitoring system.